2020
DOI: 10.1007/s12024-020-00338-w
|View full text |Cite
|
Sign up to set email alerts
|

Fatal poisoning by ingestion of a self-prepared oleander leaf infusion

Abstract: An unusual case of poisoning by the ingestion of oleander leaves is reported. A 71 year old male laboratory technician committed suicide at home in this unusual manner. At the death scene a steel pan and other paraphernalia, used for the extraction of oleandrin and other cardiac glycosides from the leaves of the Nerium oleander plant were found.Toxicological investigations for oleandrin, oleandrigenin, neritaloside, and odoroside were performed by LC–MS/MS on all biological samples (peripheral blood, vitreous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Oleandrin concentrations have been assessed in various biological samples, including the heart, bile, peripheral blood, urine, liver, and gastric content, where the LC-MS/MS detection limit reached 0.01 ng/ml. In addition, liquid-liquid extraction or solid-phase extraction was the most common pretreatment method, exhibiting the advantages of simplicity and ideal extraction recovery rate ( Tor et al, 2005 ; Wasfi et al, 2008 ; Zhai et al, 2018 ; Malysheva et al, 2020 ; Carfora et al, 2021 ). These factors make this sensitive and specific method a powerful tool for toxicology and toxicokinetics studies in humans and livestock, and may provide key information to clinicians and veterinary practitioners regarding oleandrin toxicity.…”
Section: Detection Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Oleandrin concentrations have been assessed in various biological samples, including the heart, bile, peripheral blood, urine, liver, and gastric content, where the LC-MS/MS detection limit reached 0.01 ng/ml. In addition, liquid-liquid extraction or solid-phase extraction was the most common pretreatment method, exhibiting the advantages of simplicity and ideal extraction recovery rate ( Tor et al, 2005 ; Wasfi et al, 2008 ; Zhai et al, 2018 ; Malysheva et al, 2020 ; Carfora et al, 2021 ). These factors make this sensitive and specific method a powerful tool for toxicology and toxicokinetics studies in humans and livestock, and may provide key information to clinicians and veterinary practitioners regarding oleandrin toxicity.…”
Section: Detection Methodsmentioning
confidence: 99%
“…However, oleandrin is currently the only constituent isolated from oleander that is available as a pure standard ( Tor et al, 2005 ). Other toxic components of oleander, such as neritaloside, oleandrigenin, and odoroside standards are not available commercially, and only LC/QqTOF or Orbitrap MS have been applied for their preliminary qualitative assessments in some studies ( Wang et al, 2000 ; Carfora et al, 2021 ). The identification of all the metabolites of oleandrin and other toxic components of oleander is also of great significance for the study of oleander pharmacology.…”
Section: Detection Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Carfora A et al [30] reported poisoning of oleander leaf infusion. A laboratory technician committed suicide by consuming oleander leaf infusion.…”
Section: Nerium Oleandermentioning
confidence: 99%
“…According to the investigation of 150 plant-poisoning reports in South India, oleander was suggested as the prime culprit in 65% of poisoning cases [9]. A large number of poisoning cases were also reported in the Mediterranean, where oleander is widely distributed [10][11][12]. In addition to events of human poisoning, numerous cases have also been reported in livestock due to Toxins 2022, 14, 776 2 of 10 accidental ingestion in the wild and unplanned contamination of N. oleander in feed [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%